Insulin Resistance in Patients with Polycystic Ovary Syndrome - Shazia Haider, Muhammad Ayyaz, Neha Ahuja, Maria Dhahri, Atiq Ahmad, Muhammad Faheem Siddiqui (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Polycystic ovary syndrome is a common endocrine disorder affecting women of reproductive age, characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. Objective: To determine the frequency of insulin resistance in patients with Polycystic ovary syndrome and evaluate its association with clinical features and biochemical markers. Study Design: Descriptive cross-sectional study Place and Duration of Study: Department of Obstetrics & Gynaecology, Fatima Jinnah Medical University, Lahore from 1st February 2023 to 31st July 2023. Methodology: One hundred female patients diagnosed with polycystic ovary syndrome were enrolled. Results: The mean age was 26.4±4.8 years, and mean body mass index was 29.3±5.2 kg/m². Insulin resistance was present in 68% of the patients. A significant association was observed between insulin resistance and higher body mass index (p<0.001), menstrual irregularity (p<0.01), and lipid abnormalities (p<0.05). The mean Homeostatic Model Assessment for insulin resistance in the insulin-resistant group was 4.3±1.2 compared to 2.1±0.5 in the non-resistant group. Pearson correlation showed a strong positive correlation between body mass index and Homeostatic Model Assessment for insulin resistance (r = 0.61, p<0.001). Conclusion: The insulin resistance is prevalent among women with polycystic ovary syndrome and is significantly associated with obesity, menstrual irregularities, and dyslipidemia. Routine screening for insulin resistance and early intervention are essential to prevent long-term metabolic and reproductive complications. Keywords: Insulin resistance, Polycystic ovary syndrome, Clinical features, Biochemical markers